MON-617 Improving Care Transitions: Optimizing Diabetes Medication Reconciliation - Oraibi, Omar (J Endocr Soc, 2020)
Introduction Medication reconciliation (MR) is essential in caring for hospitalized patients with diabetes (DM). Inaccuracies prevail, affecting transitions of care. Factors contributing to errors are driven by providers, patients, and systems of practice and increase in transitions out of hospital. A study showed that MR errors occurred in about 38 % of admissions. Common discrepancies among DM subjects were related to DM and cardiovascular drugs. An intervention aiming to reduce MR discrepancies at discharge achieved 70% less errors due to communication between inpatient providers, primary care and patients within 24 hours. Systems-based interventions and multidisciplinary approaches show promise to improve processes. However, a comprehensive assessment of the elements of practice to target and how interventions may be more effective is lacking. Our purpose was to examine aspects of practice among personnel responsible for the MR steps, and within the hospital workflow in order to identify gaps in the process. We intend to recognize factors to be targeted to optimize MR for DM, and to provide a multipronged approach to inform changes in hospital processes. Methods: We used quantitative and qualitative methods to investigate errors in the MR process as part of a hospital quality improvement program. We randomly included patients 18 years or older with type 1 or 2 DM evaluated by the endocrine team for 6 months. Chart reviews were conducted to assess type and frequency errors. Interviews of nurses, pharmacists, clinicians, and DM educators were sought to understand unique situations and the roles of health providers in the MR process. Results Twenty-two subjects were identified with one or more of the following gaps in their MR pertaining to DM medications: a) missing, b) redundancy, and c) dosing error. Scenarios included ≥2 discrepancies (4 of 22); ≥1 medication inappropriately changed from home regimen (18 of 22); redundantly adding a medication (4 of 22); wrong dose of medication (1 of 22); incomplete prescription for DM supplies (8 of 22). Conclusion: We identified deficits and their attribution to professionals and categorized errors in hospital workflows. Observations, providers’ insights and literature review enabled an assessment of MR failures. We developed a conceptual model where types of error, professionals’ roles, and solutions intersect Interface of prioritizing actions, hospital resources, use of checklists, interdisciplinary collaborations, and staff education is essential to advance adequate MR in the system of practice. Our future steps include a Plan-Do-Study-Act cycle to advance care.